Hybrid mathematical modeling decodes the complexity of sphingolipid pathway to predict chemosensitivity - Molina Mora, José Arturo (2017)
Forma parte de los trabajos presentado en el International Conference and Workshop on Bioinspired Intelligence (IWOBI). IEEE, Estados Unidos. Julio de 2017.